Defining research gaps concerning the implementation of socio-ecological transition - Teresa Weiss (WWWforEurope, 2016)
This paper summarizes future research questions for each driver of change based on the outcomes of the WWWforEurope project and the derived policy recommendations. Firstly, a broad research question is suggested for each driver indicating the main focus of interest. In a second step, several analytical aspects as well as policy aspects are defined to specify the broad research questions (for an overview of all analytical and policy aspects see Aiginger 2016, p. 128). While focussing on the seven drivers of change when formulating the research questions, attention was also paid to so-called cross-cutting issues (e.g. gender aspects, strategies for implementing the Paris climate agreements). The research gaps are based on the fundamental insight of WWWforEurope that highlights the importance of applying a comprehensive and integrated approach for achieving the three strategic project goals instead of following a silo approach.
Keywords: 330; Sozialer Wandel; Umweltschutz; EU-Staaten